Gaining competitive advantage through artificial intelligence adoption - Rosa, A.; Bento, T.; Pereira, L.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Electronic Business, 2022)
Companies are adopting Artificial Intelligence (AI) to be innovative, improve their strategies, and differentiate themselves from competitors. This research's objective is to examine the extent of the introduction of Artificial Intelligence in companies located in Portugal. It explores the reasons and challenges companies face to introduce it, their perception of AI, and whether they feel pressure to adopt this technology. This research uses a qualitative approach, the content analysis of twenty-one interviews with professionals familiar with the theme. This study concludes that the main challenges faced are the cost of the investment and the loss of "the human" connection with the customer. In contrast, the principal benefit is the degree of personalization Artificial Intelligence can achieve due to its ability to provide strategic information. Concerning the interviewees’ perception of this technology, 95% considers it as a competitive advantage.